Analysis on Spatial and Temporal Variation and Influencing Factors of Evapotranspiration in Lianjiang River Basin Based on the Priestley-Taylor Model - WEI Xiaocha; JIANG Yi; WEI Zhengxue; CHEN Meng; LUO Yingzhong; ZHOU Jianlong (Renmin Zhujiang)
It's of great significance foranalyzing the spatio-temporal variation characteristicsof evapotranspiration and its influencing factors on the management and utilization of water andsoil resources in the region. Based on the Priestley-Taylor model, combined with multi-sourceremote sensing data such as land surface temperature, land surface albedo, NDVI, solar zenithangle, DEM, land use and cover type, and soil type, this paper studies the spatial and temporalvariation characteristics and influencing factors of ET in the Lianjiang River Basin in GuizhouProvince from 2005 to 2014. The results show that:The Priestley-Taylor model has goodinversion accuracy in Lianjiang River Basin, with relative error of -1.39% to 12.05% and theestimation results can meet the research requirements of evapotranspiration in this area; Theannual mean ET is 901.08 mm in the study area, and it generally shows an fluctuate increasingtendency, with a change rate of 36.8 mm/(10a). The single-peak variation of ET is high in spring andsummer, and low in autumn and winter;The spatial distribution of ET in the basin is obviouslydifferent, with high in the southeast and northeast, and low in the west and middle. The spatialdistribution of ET in spring, summer and autumn is basically consistent with the multi-yearaverage spatial distribution, while the spatial distribution in winter is slightly different;The evapotranspiration intensity of different land cover types is shown as below: evergreenconiferous forest> permanent wetland> deciduous broad-leaved forest> bare land or low-coveredland> urban built-up area. In general,the evapotranspiration in high vegetation area is higherthan that in low vegetation area;The evapotranspiration intensity of different soil types isshown as below: limestone soil>yellow soil>red soil>paddy soil>purple soil. The limestone has thinsoil layer, and it has low soil moisture holding capacity, which lead to higherevapotranspiration.